Smart homerity system - Mohamad Firdaus, Mohamad (2015)
This application is name as 'Smart Homerity' where it is an anti-burglar concept implementation with using simple device and easy to get. There are act as security camera whereas the camera will captured image of the burglar, and uploaded to Dropbox and act as notified to the client as the device will send the text messaging to notifying the burglar/intruders unauthorized/ illegally enter the house. This application will worked together as a simple anti-burglar device with easy relocateable sources. These will aware the client how important is home security for their life, property and family member. There are several problem statements related to customer requirements. Clients are lack of awareness of thief protection as it is one of most favourable home crime nowadays thus this device will assists client to have security for themselves. Client will face many losses of his/her valuable properties due to not implementing any security device inside the home/workplace. Last but not least, most of the clients are comes from very busy person with difference working background, they, does not have any time to monitor their self-belonging due to its busy working hours. The objectives for this system are to design a monitoring system using Arduino, webcam and motion sensor devices; to design a SMS notification system uses an API communication, python language and AVR programming and to develop a comprehensive security system by integrating Arduino, webcam, text-messaging and cloud storage. The methodology that has been chosen is V-model. The V-model model is based on association of testing phase for each corresponding development stage. That means for each stage will have their own respectively suitable testing phase. Both verification and validation process will be used for the development as this processes will make clear path of the development process. V-model makes better understanding besides high in simplicity rather than compactness. During testing phase, User Acceptance Test (UAT) has been conducted to test the system integration and interaction between client and system behaviour. Output can be classified as a result of the system. As a result, Smart Homerity successfully detects motion from human movement, sends SMS notification via API communication, save locally images into SD card and successfully uploaded to Dropbox. PR motion sensor will detect motion when there is movement around it. From the motion detection, it will trigger the system by captured the images by using webcam. The images will be stored in SD card as a backup before upload it into the Dropbox. At the same time, a SMS notification will be send to the house owner phone number. The process will be continuously if the motion is detected.